Online simulator of learning package for networking subjects / Cheng Kok Woh - Cheng, Kok Woh (2004)
The growth of internet and multimedia services gave an impact to the student's life nowadays, a book with printed study material are no longer enough and has ultimate effective in learning process. With the ease of the internet, Information can be delivering fast and effectively. A web based as simulator is one of the solutions for educational purpose over the Internet. Online Simulator of learning Package for Networking Subjects is developed as the steps towards developing an E-Learning system for networking subjects. This system enables user learn the networking subjects via flash animation, sounds effect, and interactive with the multimedia elements. Besides, user can go through the quizzes and games provided in the system to test their understanding on networking subjects. This system includes the design and implementing the multimedia based lessons. The package is rich in multimedia, colorful pictures and animation. This will help the user complete understanding of the networking concept. This will be an effective learning tool for students to learn the networking subjects. It also can help lecturer in their teaching process, work as an extra tool to assist in curriculum.